Epidemiology of COVID-19 in Uberlândia (MG): preliminary analysis of the impact of commercial activities’s openness at different moments of the pandemic - Rosa, Maria Fernanda Prado (2020)
Introduction: The economic impact of the COVID-19’s pandemic and the interruption of several commercial activities is substantial. In Brazil, there is discussions about the need to establish periods of greater flexibility in measures of social isolation, to cover the economic’s impact in the country. In this context, effective Epidemiological Surveillance is essential. Objective: To analyze the epidemiological data of COVID-19 in Uberlândia and compare them to the municipal’s determinations of commercial opening and closing at different times of the pandemic. Methods: This is a descriptive observational epidemiological study, using secondary data, of public uses and access, of the cases notified by COVID-19 to the Municipal Health Department of Uberlândia, obtained through the Municipal Information Bulletin. Results: 59.994 tests were performed, being 14.389 positive (23.98%) and 45.605 negative (76.02%). There were 265 deaths and a fatality rate of 1.89%. The confirmed cases tended to grow after commercial openings and to stabilize after commercial closing, with a tendency to fall after the last commercial reopening, accompanied by accumulation of suspicious tests and drop in population testing. Among daily inpatients, there was a prevalence of men (59%), older than 60 years (55%) and those allocated to nursing beds (55%). Conclusion: From the analysis of the epidemiological data and the preliminary understanding of the impact of the measures adopted by the city, a significant influence of the commercial activity’s openness on the indicators of the disease was noticed. It was noticed that the frequency of positive tests and deaths increased, with maintenance of inpatients, which demonstrates the impact of this disease and the need to improve health surveillance actions in the control of the pandemic.